Regulatory role of phospholipase A2 inhibitor in oxidative stress and inflammation induced by an experimental mouse migraine model - Yazğan, Betül; Yazğan, Yener (Journal of Cellular Neuroscience and Oxidative Stress, 2023)
Migraine is a complex neurological problem whose primary symptom is headache and is common in the human population. It is well known that neuroinflammation plays a vital role in the pathogenesis of migraine, with adverse effects on the nervous system, including headache disorders such as migraine. The infusion of the nitric oxide donor glyceryl trinitrate (GTN) is often used in experimental models of migraine because it is the best-known model of migraine provocation. N-(p-amyl cinnamoyl) anthranilic acid (ACA) has been shown to inhibit both TRPM2 and phospholipase A2 (PLA2). Recent research has explored potential interventions to mitigate GTN-induced neurotoxicity. One such candidate is ACA, a compound with anti-inflammatory and antioxidant properties. Thirty-six C57BL/6j black mice were divided into the control groups of ACA, GTN, and ACA+GTN. Mice in the ACA were treated intraperitoneally with ACA (25 mg/kg) for three days. Mice in the GTN were treated intraperitoneally with a single dose of GTN (10 mg/kg) for migraine induction. After the experimental stages were completed, the mice in all groups were sacrificed, and brain tissue and erythrocyte samples were taken from the mice. The levels of inflammatory cytokines (TNF α, IL 1β, and IL 6), apoptosis, intracellular ROS, lipid peroxidation, caspase 3-9, and mitochondrial membrane potential increased in the GTN group. However, their levels were decreased in the ACA+GTN group by the injection of ACA. The treatment of ACA regulated the GTN treatment-induced decreases of glutathione levels, glutathione peroxidase activation, and cell viability in the brain and erythrocytes. In conclusion, GTN plays a role in neurotoxicity caused by increased apoptosis and ROS. We observed that ACA modulated the brain and erythrocyte oxidant, antioxidant parameters, and apoptotic processes. The neuro-protective role of ACA treatment may be explained by its modulating activity against increased apoptosis and oxidative stress.
Keywords: Apoptosis; Brain; Glutathione; Glyceryl trinitrate; Inflammatory cytokines; Sinirbilim (Diğer); Neurosciences (Other); 3. Good health